Water quality status of mangrove forest in Sungai Sepetang and Sungai Tiram Laut, Perak - Baharuddin, Muhammad Fadhli (2016)
Mangroves are unique forests that live in the area near the sea where salinity levels are high. Mangroves are also an important forest as a natural defense the waves. However these forests are increasingly threatened by human activity in the mangrove swamps. Therefore, this study was done to determine the water quality index of Sungai Sepetang and Sungai Tiram Laut near the area where human activity. The study was conducted to compare the quality of the two rivers. Data collection was taken on six parameters of WQI and five others parameters which are Ammonia-cal Nitrogen (NH3-N), chemical oxygen demand (COD), Biochemical Oxygen Demand (BOD), Oxygen (DO), pH, Total Suspended Solids (TSS), electrical conductivity (EC), turbidity (Turbidity), Total Dissolved Solids (TDS), Salinity (Salinity) and temperature. Results obtained are summarized; EC (28.25 - 36.02), pH (7.91 - 8.06), DO (2.39 - 3.76), Turbidity (11.31 - 74.29), TDS (3.31 - 21.63), SAL (2.93 - 20.74), TEMP. (28.69 - 29.86), TSS (3.00 - 4.17), BOD (0.99 - 2.08), COD (47.80 - 54.56) and NH3-N (3.38 - 7.60). Water quality index for both rivers were calculated and were in Class III, which require the treatment to the water supply.